Modulation of Tomato Response to Rhizoctonia solani by Trichoderma harzianum and Its Secondary Metabolite Harzianic Acid - Manganiello, Gelsomina; Sacco, Adriana; Ercolano, Maria R.; Vinale, Francesco; Lanzuise, Stefania; Pascale, Alberto; Napolitano, Mauro; Lombardi, Nadia; Lorito, Matteo; Woo, Sheridan L. (Frontiers in Microbiology, 2018)
The present study investigated the transcriptomic and metabolomic changes elicited in tomato plants (Solanum lycopersicum cv. Micro-Tom) following treatments with the biocontrol agent Trichoderma harzianum strain M10 or its purified secondary metabolite harzianic acid (HA), in the presence or the absence of the soil-borne pathogen Rhizoctonia solani. Transcriptomic analysis allowed the identification of differentially expressed genes (DEGs) that play a pivotal role in resistance to biotic stress. Overall, the results support the ability of T. harzianum M10 to activate defense responses in infected tomato plants. An induction of hormone-mediated signaling was observed, as shown by the up-regulation of genes involved in the ethylene and jasmonate (ET/JA) and salicylic acid (SA)-mediated signaling pathways. Further, the protective action of T. harzianum on the host was revealed by the over-expression of genes able to detoxify cells from reactive oxygen species (ROS). On the other hand, HA treatment also stimulated tomato response to the pathogen by inducing the expression of several genes involved in defense response (including protease inhibitors, resistance proteins like CC-NBS-LRR) and hormone interplay. The accumulation of steroidal glycoalkaloids in the plant after treatments with either T. harzianum or HA, as determined by metabolomic analysis, confirmed the complexity of the plant response to beneficial microbes, demonstrating that these microorganisms are also capable of activating the chemical defenses.